PERAN INSTAGRAM SEBAGAI SOCIAL MEDIA MARKETING DALAM MEMBANGUN BRAND AWARENESS UNTUK MENINGKATKAN KINERJA PEMASARAN - Chesaria, Adinda; Sunaryo, Sunaryo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The objective of this research is to identify the roles of Instagram in social media marketing, in creating brand awareness, and in improving marketing performance at Peminpin.id, a social startup. Operating in Jakarta, the startup operates in leadership ecosystem. The data of this descriptive qualitative research was harvested through interviews, observations, and documentation and was validated using triangulation. Through data reduction, data presentation, and conclusion drawing, this study finds that Instagram that is used as social media marketing can create brand awareness to enhance the marketing performance of the startup. Furthermore, the enterprise needs strategies and consistencies in order to gain maximum outcome and to avoid failures in running their programs.